Kedudukan Peraturan Pemerintah Pengganti Undang-Undang di Tinjau Dari Hierarki Perundang-Undangan Indonesia - Hanum, Roro Hanum; Murdiana, Elfa; Bahari, Raha (Siyasah, 2023)
Abstrak : In the context of law and regulations in Indonesia, the concept of hierarchy is vital for ensuring control over regulations that could potentially harm society both materially and non-materially. This concept is rooted in Hans Kelsen's theory of legal norms, which posits that legal norms have hierarchical levels, with grundnorms at the top. These norms are interrelated and form a coherent legal order. However, the application of this hierarchy is influenced by political factors that shape the constitutional system.One significant legal instrument reflecting this hierarchy in Indonesia is the Government Regulation in Lieu of Law (Perppu), which holds an equivalent position to regular laws in the Indonesian presidential system. It is essential to clearly define the term "compelling urgency" as the basis for issuing a Perppu to ensure that the President's actions remain within objective limits. Understanding and reviewing this legal hierarchy is crucial for maintaining the quality and enforcement of regulations in Indonesia. In this framework, legal comprehension revolves around official laws, and all aspects of law, norms, rules, and legal actions must align with the applicable laws. The evolution of legislation impacts various aspects of society, and a precise understanding of hierarchy and the concept of judicial review is indispensable for upholding the quality of law and justice in Indonesia.